Construction of Expert Image in Genre of Editorial: Discursive Practices - E. A. Kolomiyets (Научный диалог)
This research focuses on discursive practices employed to construct the expert image within the genre of editorial articles. The expert image aligns with the goals of this textual form. Initially, editorials served as a tool for expressing the publication’s voice and ensuring the status of an independent social institution. While this function has somewhat diminished today, editorials still play a significant role in shaping societal views and values, especially during pivotal political events. Therefore, it is crucial for authors of editorial articles to maintain authority and expert status. Research findings demonstrate that discursive practices such as referencing authoritative sources, highlighting the author’s achievements in discussing the issue at hand, presenting quantitative data, formulating predictions, and recommendations are utilized to shape the expert image in editorial articles. These practices are perceived by readers as elements of expert knowledge, yet they actually belong to distinct realms: expertise and counter-expertise. The author of the article differentiates between expertise, anti-expertise, and counterexpertise.